Increased water‐use efficiency does not lead to enhanced tree growth under xeric and mesic conditions. Issue 1 (17th March 2014) - Lévesque, Mathieu; Siegwolf, Rolf; Saurer, Matthias; Eilmann, Britta; Rigling, Andreas
Summary: Higher atmospheric CO2 concentrations ( c a ) can under certain conditions increase tree growth by enhancing photosynthesis, resulting in an increase of intrinsic water‐use efficiency (i WUE) in trees. However, the magnitude of these effects and their interactions with changing climatic conditions are still poorly understood under xeric and mesic conditions. We combined radial growth analysis with intra‐ and interannual δ 13 C and δ 18 O measurements to investigate growth and physiological responses of Larix decidua, Picea abies, Pinus sylvestris, Pinus nigra and Pseudotsuga menziesii in relation to rising c a and changing climate at a xeric site in the dry inner Alps and at a mesic site in the Swiss lowlands. i WUE increased significantly over the last 50 yr by 8–29% and varied depending on species, site water availability, and seasons. Regardless of species and increased i WUE, radial growth has significantly declined under xeric conditions, whereas growth has not increased as expected under mesic conditions. Overall, drought‐induced stomatal closure has reduced transpiration at the cost of reduced carbon uptake and growth. Our results indicate that, even under mesic conditions, the temperature‐induced drought stress has overridden the potential CO2 'fertilization' on tree growth, hence challenging today's predictions of improved forest productivity of temperate forests.